Theoretical study of the oxidation of formic acid on a PtPd(111) surface. (February 2019) - Wang, Ying-Ying
By performing density functional theory calculations, the adsorption configurations of formic acid and possible reaction pathway for HCOOH oxidation on PtPd(111) surface are located. Results show that CO2 is preferentially formed as the main product of the catalytic oxidation of formic acid. The formation of CO on the pure Pd surface could not possibly occur during formic acid decomposition on the PtPd(111) surface owing to the high reaction barrier. Therefore, no poisoning of catalyst would occur on the PtPd(111) surface. Our results indicate that the significantly increased catalytic activity of bimetallic PtPd catalyst towards HCOOH oxidation should be attributed to the reduction in poisoning by CO.